Perceptions and perspectives towards safe food handling and its practices: a case study at Jahangirnagar University - Sadia Afrin; Nahid Salma; Sabina Yeasmin; Sabah Tarin Promy; Samira Salam; Majid Khan Majahar Ali (Journal of Health, Population and Nutrition)
Abstract Background Foodborne illness is a significant public health concern, particularly in developing countries like Bangladesh. Young adults, aged 18–26 (including undergraduates and recent graduates), are especially vulnerable to the onset of unhealthy eating habits and nutritional imbalances as they begin living independently, often away from their families. This research aims to identify the risk factors associated with the knowledge, attitudes, and practices related to safe food handling among residential university students. By understanding these factors, the study seeks to inform strategies to improve food safety behaviors in this at-risk population. Methods A standardized questionnaire was administered through a simple random sampling survey of 250 students at Jahangirnagar University to collect primary data on food safety practices, attitudes, and knowledge. Descriptive statistics and the chi-square test were used to examine associations between the responses and predictor variables. To further assess the statistical significance and strength of these relationships, logistic regression analyses were performed. These methods provided a comprehensive evaluation of the factors influencing safe food handling behaviors among the students. Results The survey found that most participants were from rural areas (44.4%) and female students (65.2%). Multicollinearity issues were not detected, and predictor factors explained 53.8% (Nagelkerke R-square: 0.538) of the variation in food poisoning incidents. Overall, 57.6% of students reported being prone to food poisoning. Risk factors for food poisoning included being in the third year of study (OR: 3.493, CI: 0.394–30.972), consuming food during a blackout based on its appearance or scent (OR: 4.824, CI: 0.690–33.715), and believing food should be refrigerated for five to seven days (OR: 2.309, CI: 0.318–16.778). Conversely, students who stored raw meat or fish on the middle shelf (OR: 0.078, CI: 0.012–0.511) and those who thought leftover food should be kept in the fridge for more than seven days (OR: 0.034, CI: 0.002–0.626) were less likely to experience food poisoning. These findings highlight behaviors that influence foodborne illness risk among students. Conclusions This study found that while students in Bangladesh demonstrate a strong understanding of food handling, there has been insufficient focus on food safety education in the country. Based on these findings, the authors recommend enhancing awareness of key food safety risks and integrating this knowledge into both short- and long-term initiatives. To ensure lasting improvements in food safety, sustained and effective interventions are essential. These efforts will accelerate progress toward achieving the sustainable development goals related to public health in Bangladesh.